(untitled) (Cahiers Africains de rhétorique, 2025)
The present study on the lexical structuring of autonomy and homonymy in lyèlé, a gur language spoken in the West-Central region of Burkina Faso, precisely in the provinces of Sanguié and Boulkiemdé. The study of antonymy and homonymy falls within the field of lexicology which studies the units which constitue the lexicon of a language. She is most interested in describing the structures of lexical units. For this purpose, it can be called lexical semantics especially since she studies the meaning of the lexical units she describes. The problem of the study revolves around the following main question: how are antonyms and homonyms constructed? from this question arises the following general objective: to analyze the process of construction of antonyms and homonyms in the Lyèlé language. Our reference authors are P. Amsili (2005) and A. Lehmann (2014) who theorized about antonymy and homonymy. Their respective approaches are part of lexical semantics and lexical morphology. The study reveals that there are three categories of antonyms in the language, namely complementary or contradictory antonyms, incompatible or contrary antonyms and reciprocal or converse antonyms. As for homonyms, there are also three types : homophone homograph homonyms, heterophone homograph homonyms and grammatical homonyms.